Do Promotion, Rating, E-Store Design, and Personality Influence Impulse Buying in Generation Z and Millennials? - Wulandari, Ririn; Ngah, Abdul Hafaz (International Review of Management and Marketing, 2025)
Generation Z & Millennial is the largest internet user, also the largest e-commerce consumer in Indonesia together with the Millennial Generation. On the other hand, Generation Z & Millennial is the age group with the largest impulse buying behavior, namely around 41%. From the perspective of platform companies and traders on the platform, this is a positive phenomenon, because it can increase sales. Thus, it is necessary to test and study further the factors that influence impulse-buying behavior as a basis for developing company marketing strategies to develop target markets to other generations. Based on previous research findings and based on this, this research aims to test and analyze the influence of promotions, ratings, e-store design on online impulse-buying behavior, and personality as moderating variable. The research population is Generation Z & Millennial. The number of samples is 276. The sampling technique was carried out using a nonprobability sampling technique. An analytical method using Structural Equation Model based on Partial Least Square. The research results showed that promotion and personality each have a significant and positive effect on online impulsive buying. Meanwhile, e-store design and ratings do not have a significant and positive effect on online impulse buying. Thus, the marketing strategy needed is a promotional strategy and determining the right target market so that online impulsive buying transaction transactions increase which benefits the company.